NITROGEN AGGREGATION IN METAMORPHIC DIAMONDS FROM KAZAKHSTAN - Finnie K.S.; Fisher D.; Griffin W.L.; Harris J.W.; Sobolev N.V. (My University, 1994)
Microdiamonds that occur in high-grade metamorphic rocks of the Kokchetav massif in Kazakhstan have been interpreted as part of the metamorphic mineral assemblage, implying previously unrecorded pressures for the metamorphism of crustal rocks. Analysis of the infrared and visible absorption spectra from Kokchetav microdiamonds (extracted from recent stream sediments draining the metamorphic rocks) shows roughly 48–63% aggregation of single N substitution to A centres, but no measurable further aggregation. Calculated residence times, assuming peak metamorphic temperatures of 800–900°C, are from <0.5 Ma to 40 Ma and support the petrographic evidence that these diamonds formed during the high-pressure metamorphism, rather than being inherited from premetamorphic sediments.